2019
DOI: 10.3390/ma12091447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Plasma Gases on the Shear Bond Strength between Unfilled Polyetheretherketone (PEEK) and Veneering Composite Following Artificial Aging

Abstract: This study investigated the effect of different gaseous plasma surface treatments on the shear bond strength between unfilled polyetheretherketone (PEEK) and veneering composite resin. The study followed ISO 10477 guidelines in preparing, bonding, and testing the samples. Specimens of unfilled PEEK were distributed to one of the following six surface treatment groups: reference, adhesive, argon, nitrogen, oxygen, and air plasmas. After milling, the specimens were wet polished using (P320) polishing discs. Bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This range of shear bond strength was also reported by Younis et al for veneering composite bonded to polyetheretherketone (PEEK) 5.38 MPa–10.04 MPa [ 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…This range of shear bond strength was also reported by Younis et al for veneering composite bonded to polyetheretherketone (PEEK) 5.38 MPa–10.04 MPa [ 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…After using low-temperature plasma, a pretreated material transforms its non-polar surface into a polar surface and then a dense cross-linked layer or a rough surface is generated. These features all enhance the bonding properties [ 120 ]. Several studies focused on the plasma treatment for PEEK.…”
Section: Adhesion Of Peek To Dental Compositesmentioning
confidence: 99%
“…In addition to helium, oxygen and argon, the influence of other types of gases, such as air and nitrogen, on the improvement of PEEK bonding properties has also been studied. For example, Younis et al [ 120 ] showed that plasma treatment of nitrogen gas exerted a positive influence on the SBS of unfilled PEEK and veneering composites. Similar results after nitrogen gas plasma treatment were obtained by Fedel et al [ 124 ].…”
Section: Adhesion Of Peek To Dental Compositesmentioning
confidence: 99%
“…This limitation can be overcome by layering PEEK frameworks with composite resins to achieve a better shade and translucency. [ 8 ] Also the zirconia–feldspathic veneer interface is one of the major weak points of these restorations, and in some cases, it results in fractures, exposing the underlying zirconia. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%